Systematic review of studies which examine the flexible working practices of managers and professionals. - Anderson, Deirdre (Cranfield University, 2004)
This systematic review examines studies of flexible working practices when used by managers and professionals. The various definitions of the term “flexible working” which appear in the literature are discussed and the need for a case relevant definition in any study is put forward. Particular attention is given to spatial and temporal flexibility. The benefits and disadvantages of flexible working practices to both organizations and individuals are discussed, revealing the contradictory nature of this subject. Conflicting evidence is revealed about the effect of working in a non-traditional way on career advancement or potential, and the language used is seen as an important factor in understanding this. Theories are used to increase understanding of a field where research is very practitioner driven with little theoretical underpinning. Institutional pressures may be key factors in this organizational response to individual role conflict. Similarly, resource dependence theory, agency theory and the transaction cost perspective are considered as possible explanations for the introduction of flexible working practices as part of work/life balance policies. The importance of aligning such policies with organizational goals can be a crucial factor in their take-up and success. Theories of role conflict and identity are explored as these may inform us about the motivations of individuals in adopting such practices, linking to boundary theory which explains the segmentation or integration of work and nonwork domains. Most of the extant literature is written from the practitioner’s perspective and implications and recommendations are therefore put forward.